2008
DOI: 10.1161/atvbaha.107.160382
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Increases AT1a Receptor Expression in Abdominal Aortas to Promote Angiotensin II–Induced AAAs in Apolipoprotein E–Deficient Mice

Abstract: Objective-Castration of male apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mice reduces angiotensin II (Ang II)-induced abdominal aorta aneurysms (AAAs) to that of female mice. The purpose of this study was to determine whether this reduction is attributable to androgen-mediated regulation of aortic Ang II type 1A receptors (AT1aR). Methods and Results-AT1aR mRNA abundance in the AAA-prone region of abdominal aortas was 8-fold greater compared to thoracic aortas of male but not female mice. AT1aR mRNA abundance decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 46 publications
12
104
2
Order By: Relevance
“…75 Castrated male mice and rats treated with dihydrotestosterone and testosterone, respectively, showed a significant increase in the incidence of AAA compared with only castrated males. 69,76 Recently, a study by the same group showed that castration reduced the progressive lumen dilatation of established AAAs, suggesting that androgens also play a role in the progression of AAAs in male mice and that TGFb and Serpine1 may be targets of testosterone action in the progression of AAA. 77 In Vitro Studies Using Cultured SMCs Woodrum et al 78 examined sex differences of MMP2 in rat aortic SMCs (RASMCs).…”
Section: The Effect Of Castration On Aaa Parametersmentioning
confidence: 99%
“…75 Castrated male mice and rats treated with dihydrotestosterone and testosterone, respectively, showed a significant increase in the incidence of AAA compared with only castrated males. 69,76 Recently, a study by the same group showed that castration reduced the progressive lumen dilatation of established AAAs, suggesting that androgens also play a role in the progression of AAAs in male mice and that TGFb and Serpine1 may be targets of testosterone action in the progression of AAA. 77 In Vitro Studies Using Cultured SMCs Woodrum et al 78 examined sex differences of MMP2 in rat aortic SMCs (RASMCs).…”
Section: The Effect Of Castration On Aaa Parametersmentioning
confidence: 99%
“…Previous studies in our laboratory demonstrated that testosterone is a primary mediator of higher AAA prevalence in adult AngII-infused male mice, as orchiectomy decreased AAA incidence to the level of adult females [32]. Additional studies demonstrated a greater abundance of AT1aR mRNA in abdominal compared to thoracic aortas of male, but not female Apoe -/-mice [32].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 58%
“…Additional studies demonstrated a greater abundance of AT1aR mRNA in abdominal compared to thoracic aortas of male, but not female Apoe -/-mice [32]. Moreover, castration of male mice decreased AT1aR mRNA abundance in abdominal aortas, which was restored when castrated male mice were administered dihydrotestosterone [32].…”
Section: Inluences Of Sex Hormones On Aaa Development and Progressionmentioning
confidence: 92%
See 2 more Smart Citations